If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(3a + 14) = 90 Reorder the terms: 6(14 + 3a) = 90 (14 * 6 + 3a * 6) = 90 (84 + 18a) = 90 Solving 84 + 18a = 90 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-84' to each side of the equation. 84 + -84 + 18a = 90 + -84 Combine like terms: 84 + -84 = 0 0 + 18a = 90 + -84 18a = 90 + -84 Combine like terms: 90 + -84 = 6 18a = 6 Divide each side by '18'. a = 0.3333333333 Simplifying a = 0.3333333333
| 0=x^2-32x-5 | | B^2+5b+1= | | 1/2t+3=5 | | (5x/4)+(x+4) | | 10=0.5*2*(6+x) | | 6x+3=9(x-4) | | 8x^2y+12xy^2= | | 6x+3=9x | | 1m-5=3m | | 7/9=y+5 | | 5(c-1)+69=-3c | | 12(x+7)=4(x-1) | | 80+-2y=70 | | 4b^2-9b-34=0 | | U+4/5=-1/6 | | 0=6n-n^2 | | 30x-4=4(2x-0.3) | | -11x^2+1430x-4400=0 | | Y-7/8=-1/2 | | (x-10)+2y=70 | | 6(x-4)=-2x+24 | | 24(1/8y+37.5)+19y=1340 | | 6x+14=-7+x | | 4(x-1)=-3x+31 | | 9(3n-3)=(8n+4)+7 | | 14+6x=7-x | | 6g+7=-29 | | (2x+7)/8-2=x+(x-1)/2 | | 0=7(6-3x) | | 5.5(x-1)=0.5x+24.5 | | (t^2+7t-3)+(t^2+2t)= | | -0.3(2x-5)=0.7(6-x) |